Editorial announcements and information — ICFA Beam Dynamics Newsletter No. 83. (1st May 2022) - Cai, Y.; Piot, P.
Abstract: This is a general information article of the ICFA Beam Dynamics Newsletter No. 83. It contains two forewords from the Editor-in-Chief and the issue editor, a workshop and conference report section, a recent doctoral theses section, along with a forthcoming beam dynamics events section.